Business Model Canvas UMKM di Universitas Abdurrachman Saleh Situbondo - Mirna Amirya; Gugus Irianto (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
Being an MSME entrepreneur and being a student is both an opportunity and a challenge. The most basic thing to understand before running a business is to design an idea and one of the business proposals that is often used is the Business Model Canvas (BMC). The aim of this research is to determine the understanding of Abdurrachman Saleh Situbondo University students regarding BMC UMKM. Action research was carried out in this research and consisted of several stages, namely the planning, training and activity evaluation stages. The descriptive analysis method was used to determine their understanding regarding BMC MSMEs in nine important components of a business. The results show that BMC can help in the initial stages of validating business ideas so that future business planning is more mature and ready to be implemented. The training activities for 159 students in 2023 ran smoothly and the students were very enthusiastic about taking part in this training. In the future, it is hoped that the student participants will be able to build a BMC that contains a simple but complex description of what type of business needs to be run.